Estimation of Serum C-terminal Cross-linked Telopeptide Type II Collagen (CTX II) Level to Diagnose Early Knee Osteoarthritis - Singh S; Khanna R; Jindal D (Malaysian Orthopaedic Journal)
Introduction: This study aimed to study the usefulness of CTX II levels to identify normal population with patients of knee osteoarthritis, and its utility in identifying the severity of disease in primary knee osteoarthritis (KOA). Materials and methods: This research recruited 80 cases of KOA and 80 healthy adults (160 subjects). Patients with primary knee osteoarthritis were graded according to the KL grading system, and serum CTX II (sCTX II) value were analysed. The age, gender, and BMI of the subjects were recorded. Results: The sCTX-II value in cases (719.87 ± 256.1pg/ml) was more than in controls (419.26 ± 208.18pg/ml, p<0.001). The sCTX-II value in case group was significantly higher in males (812.67 ± 289.24) than in females (680.11 ± 236.59, p=0.03). In the control group, males (426.13 ± 221.06) and females (398.66 ± 166.92) had similar values (p=0.60). sCTX II level was higher with higher age, but this difference is significant in the case group only (p=0.003). Multivariate analysis revealed that the sCTX II level was only dependent on the severity of the disease. Analysis of the ROC curve reveals a cut-off value of sCTX II as 557.5pg/ml among cases and controls, 407.5pg/ml between KL grade 0-I, as 528.5pg/ml between KL grade I-II, as 681.1pg/ml between KL grade II-III, and as 866.4pg/ml between KL grade III-IV. Conclusion: sCTX II values are dependent only on the severity of the disease. sCTX II level estimation is an excellent diagnostic tool for identifying the normal population with knee osteoarthritis patients and has a clinical significance in identifying KOA cases of KL grade I and II.